2022
DOI: 10.3389/fpsyg.2022.1018225
|View full text |Cite
|
Sign up to set email alerts
|

Multiple wh-interrogatives in child heritage Romanian: On-line comprehension and production

Abstract: This study compared the online comprehension and the production of multiple interrogatives in 18 Romanian-English bilingual children aged 6;0–9;2 (MAGE = 8;0) living in the UK who have Romanian as heritage language (L1) and English as majority language (L2) and 32 Romanian monolingual children aged 6;11 to 9;8 (MAGE = 8;3). We examined whether differences emerge between heritage and monolingual children in the online comprehension and in the production of multiple interrogatives in Romanian, which requires fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Most of the studies comparing children's production and online comprehension have focussed on sequential bilingual children's later acquired societal language (e.g., Blom & Vasić, 2011;Chondrogianni & Marinis, 2012;Chondrogianni, Vasić et al, 2015). Bentea and Marinis (2022), however, compared online comprehension and production of fronting of Romanian wh-phrases in child heritage learners of Romanian with English as societal language. Like some of the studies testing children's societal language, Bentea and Marinis observed an asymmetry between production and online comprehension in the heritage language: bilingual children were less accurate in their production of wh-fronting in Romanian than monolingual children, but nevertheless showed similar behaviour online.…”
Section: Online Comprehension Versus Productionmentioning
confidence: 99%
“…Most of the studies comparing children's production and online comprehension have focussed on sequential bilingual children's later acquired societal language (e.g., Blom & Vasić, 2011;Chondrogianni & Marinis, 2012;Chondrogianni, Vasić et al, 2015). Bentea and Marinis (2022), however, compared online comprehension and production of fronting of Romanian wh-phrases in child heritage learners of Romanian with English as societal language. Like some of the studies testing children's societal language, Bentea and Marinis observed an asymmetry between production and online comprehension in the heritage language: bilingual children were less accurate in their production of wh-fronting in Romanian than monolingual children, but nevertheless showed similar behaviour online.…”
Section: Online Comprehension Versus Productionmentioning
confidence: 99%
“…) and D-linked 1 object wh-questions (e.g. Cerejeira 2009;Friedmann & Novogrodsky 2011;Baião 2014;Bentea, Durrleman & Rizzi 2016;Bentea 2017;a.o.). This previous research defined intervention effects in terms of featural similarity between the moved element and the intervening element (see Rizzi 2018): it has been suggested that feature identity corresponds to a configuration which is rejected by both children and adults and feature disjunction (as in the case of non-D-linked wh-questions and free relatives) is accepted and easily processed by both children and adults; in contrast, feature inclusion, as in D-linked wh-questions and headed relative clauses, is avoided by children, even though it is a possibility in the adult grammar (see the summary and general proposal in Friedmann, Belletti & Rizzi, 2009).…”
Section: Introductionmentioning
confidence: 99%